Art and urban space: Reading the contemporary Latin American city - García-Luna Romero, Ana Cristina (Street Art & Urban Creativity, 2021)
In the XXI century, the cultural sphere of urban expressions are a reflection of the perception of life in the city, of the routines and figurations that tend to relate to the urban environment and that come to shake or shape the conditions of urban life . The practice of urban art marks a drastic change within artistic movements and offers recognition to urban expressions in the bigger scale affecting the city, its identity, and its social interaction. The elaboration of this project consists of the analysis of urban art throughout the understanding of the urban system and its elements. As a case study we examined the murals produced inside the metropolitan area of the city of Monterrey, N.L., Mexico. The purpose of the documentation is to examine the relationship that each of these murals has within the urban context where they are located, achieving it through the reading of its adjacent urban elements, the study of the space where it resides and also by analyzing how these works of arts had influenced the citizens by their presence in the metropolitan context, so it can be demonstrated the impact these murals can generate, seeking the revaluation of street art within the city.